Internal wave analyzer for thermally stratified lakes. (February 2021) - de Carvalho Bueno, Rafael; Bleninger, Tobias; Lorke, Andreas
Abstract: Interwave Analyzer is an open source software that provides detailed characterization of the dynamics of internal waves in lakes and reservoirs. It is based on well-established theories and empirical knowledge on internal waves and lake mixing and facilitates a general physical classification of lakes and reservoirs. As input data, the program requires time series of water temperature from various depths and meteorological data, which can be obtained from measurements or numerical models. Interwave Analyzer performs an in-depth analysis of periodic motion by spectral analysis to identify predominant internal wave periods. To facilitate the identification of wave modes, the software is coupled with a multi-layer model. Interwave Analyzer is a powerful, easily accessible, and universal tool, which can be used for obtaining detailed understanding lake hydrodynamics not only in physical sciences, but also in the context of water quality, ecological interactions and biogeochemical fluxes in aquatic ecosystems.